An Efficient Route to Isochromene Derivatives via Cascade Radical Cyclization and Radical‐Radical Coupling. Issue 18 (25th July 2019) - Yu, Kaili; Li, Minyan; Deng, Guogang; Liu, Chunxiang; Wang, Jing; Liu, Zhengfen; Zhang, Hongbin; Yang, Xiaodong; Walsh, Patrick J.
Abstract: Isochromenes are important pharmacophores present in biologically active molecules and natural products. Their synthesis is generally limited to cyclization of phenyl propargyl ether precursors under transition metal catalyzed conditions. Herein, we present a novel disconnection that rapidly constructs isochromene derivatives through a cascade radical cyclization strategy. Generation of aryl radicals by SET reduction of 2‐iodo benzyl allenyl ethers is followed by radical cyclization to construct the isochromene core with formation of an allylic radical. The allylic radical then undergoes coupling with the azaallyl radical to give products in good to excellent yields. The elaborated 2‐iodo phenyl propargyl ether precursors can be used to construct isochromenes bearing various functional groups. Abstract :